(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The paper is based on a two-step procedure known as "Systematic Literature Network Analysis (SLNA)" (Colicchia & Strozzi, 2012): a systematic literature review (SLR) and a subsequent analysis of the subset of pertinent articles obtained through a bibliographic network analysis (NA): specifically, the citation network analysis, the co-occurrence networks analysis, and the basic statistics. The first qualitative evaluation is primarily based on the researchers' opinions regarding the choice of keywords and relies on an explanatory approach, whereas the bibliometric evaluation offers more objective insights through quantitative and statistical data (Aliyev et al., 2018). The most influential author names, journal titles, article titles, article keywords, and publication years are only a few examples of the bibliographic data examined by bibliometric approaches. The topic of the study is ovarian cancer among GenY, from reservoir of academic databases like Pubmed and Scopus, the authors have accumulated list of publications relating to keywords which are ovarian cancer, family risk, IVF and smoking which was limited to the area of medical, human, female, ovary, cancer and health